ENHANCEMENT OF STUDENTS’ MATHEMATICAL COMMUNICATION UNDER METACOGNITIVE SCAFFOLDING APPROACH - Sufyani Prabawanto (IKIP Siliwangi and I-MES, 2019)
This research aims to investigate the enhancement of students’ mathematical communication under metacognitive scaffolding approach. This research used a quasi-experimental design with pretest-posttest control. The subjects were pre-service elementary school teachers in Bandung. In this study, there were two groups of subjects: experimental and control groups. The experimental group consists of 60 students under metacognitive scaffolding approach, while the control group consists of 58 students under direct approach. Based on the prior mathematical ability, the students were classified into three levels, namely high, midlle, and low. Data collection instrument used mathematical communication test. The conclusions of the research are: (1) there is a significant difference in enhancing mathematical communication ability between students who attended the course under metacognitive scaffolding approach and those under direct approach, and (2) there was no significant interaction effect between teaching approaches and ability levels based on prior knowledge in enhancing students’ mathematical communication.